Pelatihan Penggunaan Aplikasi EndNote Sebagai Upaya Meningkatkan Kualitas Karya Tulis Ilmiah Mahasiswa - Ekaputra, Firdiawan; Amnie , Erlida; Veronika Sirait , Jeliana (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Students' skills in expressing an idea in the form of writing in the form of scientific work need to bSusing the EndNote application in improving the quality of students' scientific papers. Training activities were carried out for students of the Chemistry Education Study Program at FKIP Jambi University as a debriefing effort in preparing students' final thesis assignments. The training activities consisted of three stages of activities, namely the preparation stage, the implementation stage, and the evaluation stage. At the end of the training activities, students filled out a questionnaire regarding the evaluation of activities and the achievement of training activities. The result of this activity is an increase in students' understanding and skills in using the EndNote application in improving the quality of students' scientific papers. Based on the questionnaire filling, students assessed that the training activities carried out were very good with a score of 4.53.